Working Stress and Its’ Predictive Factors among Production Area Workers in PT X - Handayani, Putri; Millah, Izzatu; Yusvita, Fierdania (Alta Dharma Publisher, 2023)
Background: Stress is a complaint that workers in the manufacturing industry often feel. The work environment, processes, and equipment can cause work stress. The increase in workload related to the achievement of targets is one of the causes of work stress. Objective: This study aims to see the effect of workload on work stress in the production area. The variables analyzed in this study are work stress as the dependent variable, workload as an independent variable, and three confounding variables: work period, work duration, room temperature, and noise. Method: This study used an analytic observational method with a cross-sectional design approach. The sample in this study is the total population of workers in the production area, as many as 88 people. Result: The results of the bivariate analysis showed that four variables influenced work stress, workload (p=0.012), working period (p=0.002), room temperature (p=0.029), and noise (p=0.002). The results of the multivariate analysis showed that the most dominant variable affecting work stress was tenure (p=0.001 and OR=12.610). Conclusion: Management is advised to detect work stress early among employees. Recommendation: Management needs to implement an occupational health promotion program in stress management, starting with identifying the causes of stress in the work environment. In addition, it is recommended to detect work stress early in employees